Kebijakan Pemerintah Daerah dalam Penanganan Pandemi Virus Corona (COVID-19) di Kota Surabaya - Miskan Miskan; Nur Holifah (FISIP UWP, 2021)
Right on March 16, 2020, this virus has started to enter the Surabaya area. This study wants to see about the Covid-19 pandemic in Indonesia. There are two problems examined in this study. First, regarding the policies issued by the local government in overcoming the Covid-19 pandemic, especially in the city of Surabaya. Second, researchers want to see the impact of the policies issued by the Surabaya city government in dealing with the Covid-19 pandemic on the people's economy. The theory used to analyze these problems is Merilee S. Grindle's theory of public policy implementation. The research method is descriptive qualitative and the type of research is a case study. From the data analysis, it can be seen that the first finding, there are several policies issued by the Surabayacity government in dealing with the Covid-19 pandemic, namely, 1) Circular of the Mayor of Surabaya to Increase Alertness Against Covid-19 in Surabaya. 2) Population Mobility Control Protocol Based on Surabaya Mayor Circular. 3) Regulation of the Mayor of Surabaya Number 16 of 2020 concerning Guidelines for Large-Scale Social Restrictions in Handling Covid-19 in the City of Surabaya. 4) Decree of the Mayor of Surabata regarding the Task Force for the Acceleration of Handling Covid-19 in the city of Surabaya. 5) Regulation of the Mayor of Surabaya Number 28 of 2020 concerning Guidelines for the New Normal Order in the Conditions of the Covid-19 Pandemic. Second, regarding the impact of the policies issued by the Surabaya city government in handling the Covid-19 pandemic on the economy of the people of the city of Surabaya. With the implementation of large-scale social restriction policies and the temporary closure of several lower, middle and upper class shopping centers such as traditional markets, kapasan markets, Surabaya Wholesale Center (PGS), and several large malls, it has had a major impact on the economy of the community, especially the people of Surabaya who are in second place. the highest rate of covid-19 cases after Jakarta.